The Deep Content of the Form: Hayden White on “Freud’s Tropology of Dreaming” - Nancy Partner (Práticas da História, 2018)
Hayden White’s only article entirely on Sigmund Freud’s work is on The Interpretation of Dreams, specifically on the dreamwork“operations” by which the mind transforms libidinal impulses into the scenes, sounds, and events the dreamer experiences as the dream. White recognizes in Freud’s interpretive insights a clear analogy with the formal centerpiece of his own work: the major tropes which describe the shape of thought itself. White’s appreciation of how Freud’s revolutionary work on the significance of dreams uncovered the formal linguistic devices exhibited at every level of representation is shared by other major thinkers, two of whom I discuss here: the philosopher Paul Ricoeur and the psychoanalyst Marshall Edelson. They share the comprehension of how psychoanalysis illuminates the deep structure of all cultural artifacts of language as originating from sources deeper than those available to consciousness, and issuing in the formal structures of metaphor, metonymy, synechdoche, and irony.